In situ thermal reduction of graphene oxide forming epoxy nanocomposites and their dielectric properties. Issue 2 (4th March 2014) - Toselli, M.; Fabiani, D.; Mancinelli, P.; Fréchette, M.; Heid, T.; David, E.; Saccani, A.
<x xml:space="preserve">Abstract</x> The electrical properties of epoxy based composites modified by low amounts of graphite oxide, below the conduction threshold, have been investigated. The composites have been prepared without the use of solvents by direct sonication of graphite oxide (GO) powders and of chemically modified and partially reduced GO powders in the based epoxy monomer. Through a mild thermal treatment, in situ reduction of the previously dispersed GO has been obtained directly inside the epoxy resins. The changes in the electrical response of the materials thus obtained have been compared to that of pristine unmodified epoxy resin. Data so far collected underline the possibility to tune the electrical conductivity of the composites within two orders of magnitude and to increase the values of permittivity without significantly worsening dielectric losses. POLYM. COMPOS., 36:294–301, 2015. © 2014 Society of Plastics Engineers